Antigenicidade e proteção vacinal de uma proteína amastigota-específica de leishmania na leishmaniose visceral - Vivian Tamietti Martins (2013)
The acquisition of life-long immunity to the disease in recovered patients has motivated the development of studies for prophylactic vaccination against leishmaniasis. Attempting to select candidate antigens to compose a vaccine against VL, we have targeted proteins presents in the intracellular amastigote stage, which is the parasite stage that persists throughout infection with Leishmania in the mammal hosts. The present study aims to evaluate a non-described hypothetical Leishmania amastigote-specific protein, LiHyp1, which was identified by an immunoproteomic approach performed in L. infantum, in an attempt to select a new candidate antigen for a vaccine against LV. In addition, the protein LiHyp1 was evaluated with regard to their antigenicity for serodiagnosis of canine visceral leishmaniasis (CVL). In ELISA tests, the rLiHyp1 protein was recognized by antibodies present in sera samples of dogs with asymptomatic and symptomatic visceral leishmaniasis (VL), but presented no cross-reactivity when the sera from dogs with Chagas´ disease or healthy and/or vaccinated animals with Leish-Tec® were used. The immunogenicity of rLiHyp1 protein plus saponin was tested in BALB/c mice and their protective efficacy was evaluated after the challenged with L. infantum promastigotes. Mice vaccinated with rLiHyp1 presented a high production of IFN-, IL-12, and GM-CSF after in vitro stimulation with the recombinant protein. Immunized and infected mice, as compared to the control groups (saline and saponin), had a significant reduction in the number of parasites found in the liver, spleen, bone marrow, and draining lymph node in the paws. Protection was associated with an IL-12-dependent production of IFN-, produced mainly by CD4 T cells. In these mice, a decrease of IL-4 and IL-10 responses could also be observed. Therefore, the present study showed that this non-described Leishmania amastigote-specific hypothetical protein can be used for new serodiagnosis tests of CVL and, when combined with a saponin adjuvant, has proven to be useful in the protection against VL murine.